The Role Of Unismuh Halal Center in Supporting Makassar’s Halal Industry Development - Husnul Khatimah; Muhammad Najib Kasim; Sri Wahyuni (www.amertainstitute.com, 2025)
The purpose of this study was to determine the role of the Unismuh Halal Center and the opportunities and challenges faced by the Unismuh Halal Center in supporting the development of the halal industry in Makassar City. This study uses a descriptive research type with a qualitative approach. This research was conducted at the Halal Center of the Muhammadiyah University of Makassar from February 15 to March 10, 2025. Then, based on the results of the seminar and the direction of the examining lecturer, the researcher added informants and again conducted further data collection on May 25 to 27, 2025. The informants who became the sources for collecting primary data consisted of the chairman, secretary, work partners and business actors and participants from programs that had been held by the Unismuh Halal Center. Data collection was carried out by means of interviews and documentation. In this study, the data sources used in data collection included primary data and secondary data. The results of the study indicate that the Unismuh Halal Center has a very strategic role in supporting the development of the halal industry in Makassar City. The opportunities for the Unismuh Halal Center are support from the government and university leaders as well as a wide network of partners, not only nationally but also internationally. One of the biggest challenges is the lack of awareness of business actors regarding the urgency of halal certification. Based on this, the author concludes that the role of the Unismuh Halal Center greatly contributes to strengthening a sustainable, inclusive, and competitive halal industry.